(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The COVID-19 pandemic exposed vulnerabilities worldwide have amplified the call for resilient and sustainable development frameworks. This research study examines the pivotal role of local governments in Tamil Nadu to enable post-pandemic rural resilience through sustainable planning and development initiatives. This study will establish a connection between resilience, sustainability and agency by using qualitative data from government documents, and stakeholder interviews. It will show how a decentralized governance structure allowed for flexible responses to healthcare emergencies and supported sustainable livelihoods. The findings reveal that local governments played a crucial role in embedding community engagement, leveraging digital tools, building multi-sectoral structures for livelihoods and robust infrastructure undergoing the pandemic. However, several challenges surfaced in resourcing, developing responsive networks for co-designing local solutions, addressing bureaucratic inertia and socio-economic inequities. The research engages with Tamil Nadu’s broader context of rural redevelopment, and highlights how local self-governments can assist inclusive, sustainable post-COVID-19 paradigms of rural futures. The study concludes with several policy recommendations to improve institutional arrangements that support socio-economic agency for participatory planning and local governance innovation, contributing to long-term sustainability and fair equitable rural development in Tamil Nadu.